The Effect of an Online Decision-Making Skills Psychoeducation Programme on University Students’ Decision-Making Styles: A Mixed Method Study - Mutlu, Şahabettin; Kaya, Zöhre (My University, 2023)
This study examines the effect on university students’ decision-making styles of an online decision-making skills psychoeducation programme focused on cognitive behavioural therapy. A nested design, which is one of the mixed method designs, was used in the study. In the quantitative part of the study, a quasi-experimental design was used to test the effect of the programme, while in the qualitative part, a phenomenological design was used. The quantitative data of the study were obtained through the “Melbourne Decision Making Questionnaire”, while the qualitative data were obtained through a “Semi-Structured Interview Form”, “Session Evaluation Form” and “Psychoeducation Programme Evaluation Form”. The quantitative data of the study were collected from 22 participants, of whom 11 were in the experimental group and 11 were in the control group, and the qualitative data were collected from the 11 participants included in the experimental group. Descriptive statistics, exploratory and confirmatory factor analysis, reliability analysis, the Friedman rank test, the Wilcoxon signed-rank test and the Mann-Whitney U test for independent samples were used for the analysis of the quantitative data. Content analysis was performed on the qualitative data. As a result of the study, it was determined that the psychoeducation programme caused a partially significant increase in the decision-making self-esteem and vigilant decision-making style, a partially significant decrease in the avoidant decision-making style, and a significant decrease in the procrastinating decision-making style of the participants in the experimental group. However, it was observed that the psychoeducation programme did not have a significant effect on the hypervigilant decision-making style of the students in the experimental group. When the views of the participants in the experimental group about the psychoeducation programme were examined, the main views were that the content of the programme was considered satisfactory, that the programme was evaluated as an awareness-raising process, that it aroused positive and motivating emotions, and that it was a beneficial study that provided practical and tangible gains.